Immunomodulatory properties of heat-killed Rhodococcus coprophilus control the allergic reaction in a mouse model of food allergy - Rizzo, Gastón (2018)
Actinomyces are soil bacteria with immunomodulatory properties that exert biological effects on intestinal epithelial cells in different inflammatory contexts. Our goal is to study the inhibitory effect of dead Rhodococcus coprophilus-Rc on activated epithelial cells exposed to pro-inflammatory stimuli, and in an experimental food allergy model. Colon cell lines (Caco-2 and Caco-luc) were cultured with flagellin (FliC) and the induction of cytokines (IL-1b, IL-6, TNFa) and chemokines (CCL20, IL-8 and MCP-1) were studied by qPCR, while Nf-κB was analyzed by immunoblotting. In addition, Balb/c mice were sensitized with cow´s milk proteins (CMP) plus cholera toxin by gavage, and orally challenged with CMP to induce intestinal inflammation and hypersensitivity symptoms. Activated cell lines were exposed to Rc before or during activation. On the other hand, mice received Rc by gavage during one week, and then they were sensitized.. The therapeutic effect of Rc was monitored in vivo (clinical score and cutaneous test) and in vitro (serum specific antibodies and cytokines by ELISA, and cell analysis by flow cytometry). We found that Caco cells were unresponsive to dead bacteria; however, in FliC-activated cells Rc suppressed the induction of pro-inflammatory cytokines (p<0.05) and chemokines (p<0.05), with a reduced traslocation of p65 onto the nucleus. This inhibitory effect was also observed in experimental food allergy with the intragastric administration of Rc.Symptoms and serum specific IgE levels were lower in Rc-treated mice compared with sensitized mice (p<0.05), with a concomitant reduction of IL-5 (p<0.05) and intestinal CCL20 (p<0.05). In conclusion, we found that Rhodoccocus coprophilus modulated the NF-KB pathway, abrogated the production of pro-inflammatory cytokines and chemokines in intestinal epithelial cells and ameliorated hypersensitivity and the Th2-mediated immune response in the food allergy mouse model.